Respostas

2014-08-04T17:21:28-03:00
Resolvendo temo:
                     (M-3).x+4(M-5)=0...................sabe-se que x=2 substituimos
                     (M-3)2+4(M-5)=0.........multiplicando temos:
                      2M-6+4M-20=0..........somando termos comuns
                         6M-26 =0
                          6M=26
                            M=26/6..........podemos simplificar ou divir por 2 o numerado e denominador          M=13/3.............Rsta.
                                                  
                                                                            espero ter ajudado!!